Human capital scheme in Maharashtra (India) - Tashenova, A.; Tattymbetova, K.; Rakhmetova, A.; Tukeyev, A. (KU Publ., 2021)
Object: The main objective of this paper is to try and ascertain how far the implementation of EGS in Maharashtra state has been effective as an instrument to reduce poverty. Methods: The method focuses on just two «theories of change» due to a shortage of space, namely, income maintenance and addressing exclusion as underpinning anti-poverty transfer. Trends in poverty and the drawbacks of the project will also be examined via literature review of articles and reports. Findings: The «win-win» approach of the government has created employment opportunities for poor people, improving the rural infrastructure and involving vulnerable groups within society in the project. This represents a successful example of an anti-poverty programme, as adopted in different developing countries of Asia and Africa, to reduce the high levels of chronic poverty. However, such a scheme operating in isolation cannot rapidly alleviate poverty. Conclusions: EGS reduces poverty, reflecting on the experience of the scheme’s implementation in Maharashtra state. In order to successfully combat chronic poverty in developing countries’ government institutes need to establish strong, comprehensive and effective strategies to benefit anti-poverty transfer programmes. Maharashtra state has excelled in this respect. Targeted cash transfers in the form of public works have greatly reduced poverty in rural districts of the state.
Махараштрадағы адам капиталының схемасы (Үндістан)
Схема человеческого капитала в Махараштре (Индия)
Keywords: human capital; policy strategy; poverty; anti-poverty programmes; sustainability; policy; Employment Guarantee Scheme